2017
DOI: 10.3390/su9050855
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Planning Control on Urban Growth: Evidence from Hangzhou, China

Abstract: Urban sprawl presents a serious challenge for sustainable urban land use. Urban planning attempts to guarantee sustainable urban development and proper use of land resources. However, a large gap usually exists between planning and actual development. This paper aims to analyze the evolutionary characteristics of urban form and the spatiotemporal dynamics of urban planning from 1964 to 2013, using the case of Hangzhou, China. We proposed a framework that included remote sensing, landscape metrics, and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…Regarding the evaluation of the effectiveness of land use policy, Wu et al [12] have established a comprehensive index system that can analyze land use planning results from many aspects such as scale, structure, and pattern. Thus, we can carry out dynamic analysis on the actual effect of land use policy, and land use policy can not only find the gap with the actual demand, but also make the targeted improvement and improve the efficiency of land use.…”
Section: Methodologies For Analyzing Land Use Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the evaluation of the effectiveness of land use policy, Wu et al [12] have established a comprehensive index system that can analyze land use planning results from many aspects such as scale, structure, and pattern. Thus, we can carry out dynamic analysis on the actual effect of land use policy, and land use policy can not only find the gap with the actual demand, but also make the targeted improvement and improve the efficiency of land use.…”
Section: Methodologies For Analyzing Land Use Issuesmentioning
confidence: 99%
“…Based on an empirical analysis, Wu et al [12] have found that large-scale expansion of cities is now a very common phenomenon, which leads to many urban development problems, especially the problem of the shortage of land resources. This issue also hinders increasing land use intensity and realizing the sustainable utilization of land.…”
Section: Sustainable Use Of Urban Landmentioning
confidence: 99%
“…The results of the self-organization process are mainly reflected in outward expansion trends driven by insufficient space in the city centre. The process of being organized is mainly embodied in the government's overall plan for urban spatial structures and construction of mass agglomeration areas for producer service sectors in multi-type city renewal [60]. The approximation to CBD and sub-centers, science parks, and other special policy areas have the largest influence on site selection for producer service sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Strategic spatial planning research, consequently, must explore ways to better propose planning interventions and spatial strategies that support the transformation of brownfields [105][106][107], as well as effectively devise growth-management policies [108] and restrict urban sprawl [109]. Brownfield land, for example, can be defined as land that has previously been developed, but which is not in current active use or remains vacant for redevelopment [105,106].…”
Section: Future Research Directionsmentioning
confidence: 99%
“…More research is also needed on how to effectively integrate growth-management policies, like those intended to control urban sprawl, into strategic spatial planning. Existing research reveals that establishing rigorous restrictions and heavy financial penalties on development activities that occur outside the planning boundary could contain urban sprawl [109]. Yet doubts remain as to whether these types of financial schemes are truly effective in today's context of speedy urbanization and the growing pressures of private economic actors on the consumption of fertile agriculture land, as well as on greenfields in general.…”
Section: Future Research Directionsmentioning
confidence: 99%